A Transcriptomic and Proteomic Analysis of the Diaphorina citri Salivary Glands Reveals Genes Responding to Candidatus Liberibacter asiaticus - Liu, Xiao-Qiang; Jiang, Hong-Bo; Liu, Tian-Yuan; Yang, Li; Fan, Jia-Yao; Xiong, Ying; Jing, Tian-Xing; Lou, Bing-Hai; Dou, Wei; Wang, Jin-Jun (Frontiers in Physiology, 2020)
The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, is the principal vector of the Candidatus Liberibacter asiaticus (CLas) bacterium that causes Huanglongbing (HLB) disease. The D. citri salivary glands (SG) is an important barrier to the transmission of CLas. Despite its importance, the transcriptome and proteome of SG defense against CLas are unstudied in D. citri. In the present study, we generated a comparative transcriptome dataset of the SG in infected and uninfected D. citri using an Illumina RNA-Seq technology. We obtained 407 differentially expressed genes (DEGs), including 159 upregulated DEGs and 248 downregulated DEGs. Functional categories showed that many DEGs were associated with the ribosome, the insecticide resistance, the immune response and the digestion in comparison with CLas-infected SG and CLas-free SG. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases confirmed that metabolism and immunity were important functions in the SG. Among the DEGs, 68 genes (35 upregulated and 33 downregulated) encoding putative-secreted proteins were obtained with a signal peptide, suggesting that these genes may play important roles in CLas infection. A total of 673 SG proteins were identified in uninfected D. citri by liquid chromatography-mass spectrometry/mass spectrometry (LC−MS/MS) analysis, and 30 DEGs (15 upregulated and 15 downregulated) were found using the local tBLASTP programs. Among the 30 DEGs, many DEGs mainly involved in the metabolism and cellular processes pathways. This study provides basic transcriptome and proteome information for the SG in D. citri, and helps illuminate the molecular interactions between CLas and D. citri.